PCR detection of haemolysin gene of Streptococcus suis type 2 - MA You-zhi; LI Xiao-liang; FANG Wei-huan (浙江大学学报. 农业与生命科学版)
A PCR assay for rapid and sensitive detection of haemolysin of Streptococcus suis type 2 was established. The PCR primers based on the haemolysin of S. suis type 2 succeeded in amplifying a 1502 bp PCR product. The PCR product could be digested into two fragments of 869 bp and 633 bp by EcoR I. With the nested PCR, a 1443 bp fragment was produced. No PCR product was extended from Streptococcus equi subsp. zooepidemicus, Erysipelothrix rhusiopathial and Actinobacillus. suis. The PCR technique could detect as low as 100 bacterial cells. The results show that haemolysin-based PCR is a highly specific and sensitive diagnostic tool for detection of S. suis type 2.